Factors affecting use of e-procurement system amongst employees at Naza Eftra Trading / Norhayati Baharudin - Baharudin, Norhayati (Faculty of Business and Management, 2015)
This paper is concerned with the factors affecting the use of e-procurement among employees in Naza Eftra Trading. The area of interests involved are; Perceived Ease of Use, Perceived Usefulness, Attitudes towards use of e-procurement. The tree independent variables were developed from the Technology Acceptance Model (Tam). 100 questionnaires were administered among several employees at the firms. Findings have shown that the three independents variables supported the hypotheses thus it is a factor that affecting the usage of e-procurement. Further discussions and recommendations are proposed in order to improve the underlying problems.